2020
DOI: 10.1109/jtehm.2020.2973973
|View full text |Cite
|
Sign up to set email alerts
|

Novel EM Guided Endovascular Instrumentation for In Situ Endograft Fenestration

Abstract: Objective: This work aims at providing novel endovascular instrumentation to overcome current technical limitations of in situ endograft fenestration including challenges in targeting the fenestration site under fluoroscopic control and supplying mechanical support during endograft perforation. Technology: Novel electromagnetically trackable instruments were developed to facilitate the navigation of the fenestration device and its stabilization at the target site. In vitro trials were performed to preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Recently, another group has demonstrated the use of a de novo trackable and steerable catheter for in situ fenestration. 6 The catheter had a bendable catheter tip allowing for 90° bend to allow for perpendicular positioning to the stent graft. The catheter was tested in a rigid model with good technical success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another group has demonstrated the use of a de novo trackable and steerable catheter for in situ fenestration. 6 The catheter had a bendable catheter tip allowing for 90° bend to allow for perpendicular positioning to the stent graft. The catheter was tested in a rigid model with good technical success.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Recently, the combination of EM tracking with steerable catheters or sheaths has been proposed for complex cannulation tasks. 5 , 6 In a further attempt to combine the agility of a steerable catheter with the 3D visualization provided with EM tracking, a steerable catheter with an embedded EM sensor was developed. 7 The aim of this swine model study was 2-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular ultrasound probes were not able to visualize the renal orifices for fenestration both within the stent graft and within the inferior vena cava[ 6 ]. However, electromagnetically guided endovascular instrumentation was successful in in vitro trials[ 11 , 12 ]. Therefore, in our case, fenestration was performed while the stent graft was positioned well with the bare stent region unreleased, allowing real-time positioning by angiography.…”
Section: Discussionmentioning
confidence: 99%
“…If endovascular therapy is deemed to be the best treatment option, antegrade ISF may be an ideal method to preserve the patency of visceral arteries. Many animal experiments[ 6 - 9 ], benchtop studies[ 10 - 12 ], and clinical studies[ 13 - 17 ] have demonstrated that the antegrade ISF of aortic stent grafts during EVAR is technically feasible. The following report describes a novel approach of antegrade in situ laser fenestration (ISLF) during EVAR.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce radiation and contrast dose, electromagnetic (EM) tracking of instruments with registration to preoperative computed tomography angiography (CTA) can be an appealing supplement. EM tracking has been demonstrated in feasibility studies, including in-situ fenestration of stent graft and cannulation of branch vessels (1)(2)(3)(4)(5)(6)(7). Most reported results are from in vitro phantom experiments, some from in-vivo animal studies, but very limited from patients.…”
Section: Introductionmentioning
confidence: 99%